Against the sky ebook - Martin, Kat (Brodies of Alaska,, 2015)
New York Times -Bestselling Author: A man and woman face down kidnappers and killers in the northern wilderness in this tale of romantic suspense. Detective Nick Brodie works at keeping the perps off the streets of Anchorage 24/7. Nick has never backed down from danger, but after the horrors he's seen, he's definitely in need of a break. Samantha Hollis never thought she'd meet anyone like Nick, especially in a place like Las Vegas. But after one reckless, passionate night, she discovers the charismatic stranger is everything she wants in a man. But can he ever be anything more than a one-night stand? When Nick invites her to Alaska, Samantha decides to find out, never guessing the depths she'll discover in him or the tangle of murder, kidnapping, and danger about to engulf them both . . . "I love her books." —Linda Lael Miller, #1 New York Times -bestselling author of Country Strong